High-strength and high-toughness lignin-based liquid crystal elastomer as well as preparation method and application thereof
The one-pot synthesis of lignin-based liquid crystal elastomers has solved the problem of insufficient mechanical properties of liquid crystal elastomers, achieving high mechanical strength and UV radiation resistance, making them suitable for industrial production.
Patent Information
- Application Number
- CN202511050259.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-10-21
- Estimated Expiration
- 2045-07-29
AI Technical Summary
Existing liquid crystal elastomers have shortcomings in mechanical properties, making it difficult to meet the application requirements of high-load scenarios such as artificial muscles. Traditional synthesis methods are cumbersome or have degraded mechanical properties.
A one-pot method was used to synthesize lignin-based liquid crystal elastomers. Hydroxyl-terminated liquid crystal polyols were prepared by reacting liquid crystal units with hydroxythiols, and then reacted with isocyanates and lignin to form liquid crystal-polyurethane prepolymers. High-mechanical-strength liquid crystal elastomers were obtained by hot pressing.
The mechanical properties of liquid crystal elastomers have been improved, with tensile strength and toughness reaching the highest levels to date. They also possess excellent resistance to ultraviolet radiation and reprocessing properties, making them suitable for large-scale industrial production.
Smart Images

Figure BDA0005522910650000091 
Figure BDA0005522910650000181 
Figure HDA0005522910660000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid crystal elastomer materials, and in particular relates to a high-strength and high-toughness lignin-based liquid crystal elastomer and a preparation method and application thereof. Background Art
[0002] Liquid crystal, an ordered phase between liquid and crystalline, combines the fluidity of liquids with the anisotropy of crystalline molecules. Liquid crystal elastomers (LCEs) are produced by bonding mesogens to a cross-linkable polymer backbone and curing them. Due to the ordered orientation of these mesogens, these materials exhibit unique properties such as stimulus-responsive actuation and anisotropic deformation. This contactless actuation capability holds significant potential for applications in soft robotics, intelligent gripping devices, and artificial muscles.
[0003] At present, the synthesis of LCE mainly consists of step-by-step polymerization and one-step direct cross-linking. The former is an early and more widely used synthetic method. First, a low-cross-linked LCE gel is prepared by prepolymer, and then uniaxial stretching is used to induce mesogen orientation. Secondary curing is performed under the premise of maintaining strain locking. This method is mature but the steps are cumbersome, and the orientation stability is restricted by the degree of curing, making it difficult to erase and reconstruct. The latter introduces some dynamic units to polymerize and cure LC with chain extenders and cross-linkers in one step. This method simplifies the orientation process, breaks through the limitation of force field dependence, and expands the multi-field response orientation path such as light / heat. It has gradually become a research hotspot in recent years.
[0004] Patent application CN119081117A discloses a method for preparing a near-infrared light-responsive liquid crystal elastomer with dual dynamic bond cross-linking. By introducing dopamine hydrochloride monomer and coordination system, an LCE with excellent photothermal conversion performance is obtained, but the mechanical strength of the material is only 5-6MPa.
[0005] Patent application CN118879072A discloses a liquid crystal elastomer with good damping performance, good flexibility and ductility. Through the synergistic effect of the chain movement of linear polymers and the phase transition of liquid crystal elements, it can jointly absorb and dissipate vibration energy. However, the tensile strength of the material is only 4-5MPa.
[0006] Yang Huai et al. (Chemical Engineering Journal 2024, 491:152185) synthesized a novel aromatic disulfide bond molecule (DSAC) and coated it with an AC-MWCNTs@Ag / PVDF functional layer, developing a liquid crystal elastomer soft actuator with both self-healing properties and multi-mode optical / electrical / thermal actuation. This material can achieve complex three-dimensional deformation under near-infrared light. However, its mechanical strength is severely limited: the tensile strength of the base material MLCE-2 is only 0.48 MPa.
[0007] Lignin, a naturally abundant biomass resource, contains benzene rings and abundant hydroxyl groups within its molecules. The π-π stacking between these rings not only serves as a rigid hard segment in polymer materials, but also enhances their mechanical properties and enables excellent photothermal conversion. Therefore, introducing these chemical crosslinks into LCEs can enhance the material's mechanical strength while also enabling photothermal actuation.
[0008] Given the functional positioning of LCE in mechanical applications such as artificial muscles, the material should possess good mechanical properties. However, current research has limited the use of LCE in step-by-step methods due to the oriented solidification process, making it difficult to construct a highly cross-linked network. Furthermore, the dynamic weak bonds introduced by the one-step method dilute the cross-link density, leading to a decrease in mechanical properties. This contradiction severely restricts the expansion of LCE applications in high-load scenarios such as artificial muscles. Summary of the Invention
[0009] In order to address the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a lignin-based photothermal liquid crystal elastomer with high mechanical properties.
[0010] The lignin-based liquid crystal elastomer prepared by the present invention exhibits high strength and toughness, excellent elasticity, aging resistance, and UV shielding properties. This invention overcomes the shortcomings of conventional liquid crystal elastomers, such as low strength, difficulty in intrinsic photothermal generation, and the high use of petroleum-based chemicals during synthesis. Furthermore, the lignin extraction process employed in the present invention is simple and easy to operate, making it suitable for industrial mass production. Furthermore, the synthesis of the liquid crystal elastomer requires a one-pot prepolymerization and chain extension process to produce a cross-linked liquid crystal elastomer.
[0011] Another object of the present invention is to provide a lignin-based liquid crystal elastomer with high mechanical strength prepared by the above method.
[0012] Another object of the present invention is to provide an application of the above-mentioned lignin-based liquid crystal elastomer with high mechanical strength.
[0013] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0014] In a first aspect, the present invention provides a method for preparing a high mechanical strength lignin-based liquid crystal elastomer, comprising the following steps:
[0015] (1) reacting a liquid crystal unit with a hydroxy mercaptan in the presence of a base catalyst to prepare a hydroxyl-terminated liquid crystal polyol;
[0016] (2) reacting polyol and isocyanate in the presence of a catalyst to synthesize a liquid crystal-polyurethane prepolymer, then adding lignin to continue the reaction, and drying and hot-pressing the resulting product to obtain a lignin-based liquid crystal elastomer;
[0017] The polyol is a hydroxyl-terminated liquid crystal polyol, or a mixture of a hydroxyl-terminated liquid crystal polyol and a long-chain polyol.
[0018] Preferably, in step (2), the molar ratio of -NCO of the isocyanate to the total hydroxyl groups in the polyol and lignin is 1:1 to 1.6:1 (e.g., 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, etc.); the mass ratio of lignin to polyol is 2.5:97.5 to 20:80 (e.g., 2.5:97.5, 5:95, 7.5:92.5, 10:90, 15:85, 20:80, etc.); and the molar ratio of the long-chain polyol to the hydroxyl-terminated liquid crystal polyol is 0 to 0.5:1 (e.g., 0:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0019] Preferably, the liquid crystal unit in step (1) includes at least one of 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene, 2-methyl-1,4-phenylenebis(4-((11-(acryloyloxy)undecyl)oxy)benzoate) and 1,4-bis-[4-(3-acryloyloxypropoxy)benzoyloxy]-2-methylbenzene.
[0020] Preferably, the hydroxy mercaptan in step (1) comprises at least one of 2-mercaptoethanol, 3-mercapto-1-propanol, 5-mercapto-1-pentanol and 6-mercapto-1-hexanol.
[0021] Preferably, the molar ratio of the liquid crystal unit to the hydroxythiol in step (1) is 1:(1.5-3.5) (e.g., 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0022] Preferably, the reaction medium in step (1) is an organic solvent, and the organic solvent includes at least one of ethyl acetate, dichloromethane, acetone, methanol, tetrahydrofuran and acetonitrile.
[0023] Preferably, the concentration of the liquid crystal unit in the organic solvent is 0.1-0.3 mol / L (eg, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, etc.) Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0024] Preferably, the catalyst in step (1) comprises at least one of triethylamine, di-n-propylamine, triethanolamine, 1,8-diazabicyclo[5.4.0]undec-7-ene and triethylenediamine.
[0025] Preferably, the amount of the catalyst used in step (1) is 1 to 2 equivalents of the liquid crystal unit (e.g., 1 times, 1.5 times, 2 times, etc., of the amount of the liquid crystal unit substance). Any other specific point value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0026] Preferably, the reaction temperature in step (1) is 0-40°C (e.g., 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.), and the reaction time is 10-24h (e.g., 10h, 12h, 15h, 18h, 20h, 22h, 24h, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0027] Preferably, after the reaction in step (1) is completed, the product is separated and purified by column chromatography, wherein the developing solvent for the column chromatography separation and purification is at least one of ethyl acetate / petroleum ether, acetone / petroleum ether, and dichloromethane / methanol.
[0028] Preferably, the long-chain polyol in step (2) comprises at least one of polytetramethylene glycol, polycaprolactone glycol and polycarbonate diol.
[0029] Preferably, the weight average molecular weight of the long-chain polyol in step (2) is 1000-2000 (e.g., 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0030] Preferably, the isocyanate in step (2) includes at least one of pentamethylene diisocyanate (PDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI) and hexamethylene diisocyanate trimer.
[0031] Preferably, the catalyst in step (2) comprises a conventional tin catalyst, further comprising at least one of dibutyltin dilaurate, dibutyltin oxide, di(dodecylsulfide)dibutyltin, stannous octoate, and monobutyltin oxide; the amount of the catalyst used is 0.3-0.8% (e.g., 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, etc.) of the total mass of the raw materials. Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0032] Preferably, the hydroxyl-terminated liquid crystal polyol in step (2) is subjected to vacuum dehydration at 90-120° C. (e.g., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., 120° C., etc.) for 1-3 hours (e.g., 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc.) before the reaction. Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0033] Preferably, the temperature of synthesizing the liquid crystal polyurethane prepolymer in step (2) is 60-80° C. (e.g., 60° C., 65° C., 70° C., 75° C., 80° C., etc.), and the time is 2-3 hours (e.g., 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0034] Preferably, the synthesis of the liquid crystal polyurethane prepolymer in step (2) and the addition of lignin for continued reaction are both carried out under an inert gas atmosphere, wherein the inert gas comprises at least one of nitrogen, argon and helium.
[0035] Preferably, the lignin in step (2) is a specific molecular weight lignin having a weight average molecular weight (Mw) of 700 to 2000 (e.g., 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, etc.), and a molecular weight distribution index of less than or equal to 2.4 (e.g., 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0, 2.2, 2.4, etc.); more preferably, less than 2.0. Any other specific point value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0036] The specific molecular weight lignin is obtained by the following method: fully dissolving industrial lignin in an organic solvent, filtering and separating the filtrate, removing the organic solvent in the filtrate, and drying to obtain the specific molecular weight lignin.
[0037] The temperature of the solvent is 20-100° C. (e.g., 20° C., 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., etc.), and the reaction time is 1-10 h (e.g., 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0038] The concentration of the industrial lignin and the organic solvent after mixing is 100 to 1000 g / L (e.g., 100 g / L, 200 g / L, 300 g / L, 400 g / L, 500 g / L, 600 g / L, 700 g / L, 800 g / L, 900 g / L, 1000 g / L, etc.). Any other specific point value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0039] The industrial lignin includes at least one of enzymatic lignin extracted from ethanol production by fermentation of wood fibers, alkali lignin as a by-product of alkali pulping, and organic solvent lignin extracted from wood fibers.
[0040] The organic solvent includes at least one of tetrahydrofuran, acetone, butanone, methanol, isopropanol, ethyl acetate, ethanol, ether and hexane, or a mixture of at least one of these solvents and water.
[0041] The drying temperature is 40-80° C. (e.g., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., etc.) Any other specific value within the above numerical range can be selected, which is not convenient to describe here.
[0042] Preferably, the temperature for continuing the reaction by adding lignin in step (2) is 60-90° C. (e.g., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., etc.), and the reaction time is 4-7 h (e.g., 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0043] Preferably, the drying in step (2) refers to drying in air first and then heating and drying, wherein the air drying temperature is 10-40°C (e.g., 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.), and the drying time is 48-72h (e.g., 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h , 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, etc.); the heating and drying temperature is 55-75°C (for example, 55°C, 65°C, 75°C, etc.), and the time is 24-48h (for example, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, etc.). Any other specific point value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0044] Preferably, the temperature of the hot pressing molding in step (2) is 130-180° C. (e.g., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., etc.) Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0045] Preferably, the pressure of the hot pressing molding in step (2) is 10-12 MPa (e.g., 10 MPa, 10.5 MPa, 11 MPa, 11.5 MPa, 12 MPa, etc.), and the time is 15-20 min (e.g., 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0046] Preferably, the medium of the reaction in step (2) is a polar organic solvent, and the polar organic solvent includes at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC) and dimethyl sulfoxide (DMSO).
[0047] Preferably, the total concentration of the polyol and lignin in the organic solvent in step (2) is 0.1 to 0.4 g / mL (e.g., 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, etc.). Any other specific value within the above numerical range can be selected, and it is not convenient to repeat them one by one here.
[0048] Preferably, the method for preparing the high mechanical strength lignin-based liquid crystal elastomer comprises the following steps:
[0049] (1) industrial lignin is mixed with an organic solvent, stirred at 20-100°C for 1-10 hours, filtered and separated, the filtrate is collected and the solvent is removed, and dried to obtain a specific molecular weight lignin;
[0050] (2) dissolving the liquid crystal unit and the hydroxythiol in an organic solvent, stirring and mixing at 0-40° C., adding a base catalyst, stirring and reacting for 10-24 hours, and purifying the obtained product to obtain a hydroxyl-terminated liquid crystal polyol;
[0051] (3) Dehydrating the liquid crystal polyol at 90-120° C., then cooling to 60-80° C., adding an organic solvent, a long-chain polyol, a catalyst, and an isocyanate to synthesize a liquid crystal-polyurethane prepolymer, and then adding lignin of a specific molecular weight to the liquid crystal-polyurethane prepolymer, stirring and reacting for 4-7 hours. After drying the obtained product, hot pressing at 130-180° C. to obtain a lignin-based liquid crystal elastomer.
[0052] In a second aspect, the present invention provides a lignin-based liquid crystal elastomer having excellent mechanical properties obtained by the above method.
[0053] In a third aspect, the present invention provides an application of the above-mentioned lignin-based liquid crystal elastomer.
[0054] The application in the field of artificial muscles is preferred.
[0055] The specific molecular weight lignin prepared by the present invention has a smaller molecular weight and a more uniform distribution than the untreated industrial lignin raw material, has more reactive sites, and is more compatible with the polyurethane matrix. Thanks to its rigid aromatic ring structure and multifunctional characteristics, the mechanical properties of the liquid crystal elastomer are effectively enhanced. The preparation process of the liquid crystal polyol is mild and the method is simple, with a high conversion rate and even no need for further purification. In the elastomer synthesis process, lignin polyol is used to replace part of the liquid crystal polyol to synthesize the lignin-based liquid crystal elastomer. Lignin forms a nano-microphase separation structure in the liquid crystal elastomer, and the lignin microphase is connected to the liquid crystal elastomer matrix by covalent bonds. The system has good compatibility and greatly improves the mechanical properties of the material. In addition, the specific molecular weight lignin prepared by the present invention also gives the liquid crystal-polyurethane elastomer better anti-ultraviolet radiation and heavy processing performance, as well as photothermal response function.
[0056] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0057] 1. The present invention modifies the commercially available liquid crystal unit so that it can be well incorporated into the polyurethane matrix. The rich benzene ring structure of the liquid crystal unit can form a stronger conjugation effect with lignin, further improving the mechanical properties of the material under the intrinsic enhancement effect of lignin.
[0058] 2. The liquid crystal elastomer prepared by the present invention has excellent mechanical properties, and its tensile strength, toughness and modulus all reach the highest level in the current liquid crystal elastomer field.
[0059] 3. The lignin raw material described in the present invention is abundant, inexpensive, widely available, non-toxic, and biodegradable. Compared to polythiol crosslinkers, it is more environmentally friendly. Furthermore, lignin imparts improved mechanical properties, UV and aging resistance, thermal stability, and photothermal responsiveness to the liquid crystal elastomer.
[0060] 4. The present invention uses a low-boiling-point, low-toxic organic solvent to extract lignin of a specific molecular weight. The process is simple and easy to operate, suitable for industrial large-scale production of low-molecular-weight lignin. It overcomes the time-consuming, labor-intensive, and costly shortcomings of conventional chemical modification of lignin. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 In the case of (a), RM82-OH 1 H NMR spectrum; (b) RM82-OH 12C NMR spectrum; (c) FT-IR spectra of RM82 before and after modification in Example 4.
[0062] Figure 2 In the figure, (ab) are the effects of different R values in Examples 4 and 7-9 and different lignin substitution amounts in Examples 1-6 on the mechanical properties of LCE-PU; (c) is the summary of Young's modulus and toughness of different formulas in Examples 1-4; (d) is the effect of introducing long-chain polyols on the mechanical properties of LCE-PU in Examples 4 and 10-11.
[0063] Figure 3 In the figure, (a) is the UV-visible transmittance curve of LCE-PU with different lignin additions in Examples 1-4; (bc) are the mechanical property comparison and stress-strain retention of AOH10 R1.2 before and after UV aging at 50°C for 3 days in Example 4. DETAILED DESCRIPTION
[0064] The present invention will be described in further detail below with reference to examples and drawings, but the embodiments of the present invention are not limited thereto.
[0065] The materials involved in the following examples can be obtained from commercial channels.
[0066] Tensile test conditions: The hot-pressed elastomer was cut into standard dumbbell-shaped bars with a length of 50 mm, a width of 4 mm, and a thickness of 0.5 mm. The tensile gauge length was 20 mm. A CMT electronic universal testing machine was used, the test temperature was room temperature, and the tensile rate was 100 mm / min.
[0067] 800 g of alkali lignin was dissolved in 5 L of ethanol aqueous solution, stirred at 25° C. for 4 h, filtered and separated, and the filtrate was taken and the solvent was removed, and vacuum dried at 55° C. to obtain specific molecular weight lignin.
[0068] Table 1 Characteristic parameters of alkali lignin (AKL) and solvent extracted lignin (AOH)
[0069]
[0070] As shown in Table 1, compared with the alkali lignin raw material (AKL), the molecular weight of the purified alkali lignin (AOH) is significantly reduced, the hydroxyl content is increased, and the distribution is more uniform.
[0071] Example 1
[0072] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product (RM82-OH) can be obtained.
[0073] (2) 9.75 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 0.25 g of AOH previously dissolved in about 15 mL of DMF was then added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0074] Example 2
[0075] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0076] (2) 9.5 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 0.5 g of AOH previously dissolved in about 15 mL of DMF was then added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0077] Example 3
[0078] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0079] (2) 9.25 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 0.75 g of AOH previously dissolved in about 15 mL of DMF was then added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0080] Example 4
[0081] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0082] (2) 9 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 1 g of AOH previously dissolved in about 15 mL of DMF was added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0083] Example 5
[0084] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0085] (2) 8.5 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 1 g of AOH dissolved in about 15 mL of DMF was added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0086] Example 6
[0087] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0088] (2) 8 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 2 g of AOH previously dissolved in about 15 mL of DMF was then added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0089] Example 7
[0090] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0091] (2) 9 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.0, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 1 g of AOH previously dissolved in about 15 mL of DMF was added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0092] Example 8
[0093] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0094] (2) 9 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.4, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 1 g of AOH previously dissolved in about 15 mL of DMF was added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0095] Example 9
[0096] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0097] (2) 9 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.6, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 1 g of AOH previously dissolved in about 15 mL of DMF was added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0098] Example 10
[0099] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0100] (2) 9 g of a mixture of liquid crystal unit polyol and polytetrahydrofuran diol (molecular weight 2000) was placed in a three-necked flask, wherein the amount of polytetrahydrofuran diol was 0.5 times that of the liquid crystal polyol. About 10 mL of N,N-dimethylformamide (DMF) was added, stirred and dissolved at 100° C. and vacuum dried for 2 h. The temperature was then lowered to 70° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in all polyols and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70° C. for 2 h. 1 g of AOH previously dissolved in about 15 mL of DMF was then added, and the temperature was raised to 90° C. The reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70° C. for 48 h. The sample was heat treated at 170°C and 11 MPa for 10 min using a flat vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0101] Example 11
[0102] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0103] (2) 8.5 g of a mixture of liquid crystal unit polyol and polytetrahydrofuran diol (molecular weight 2000) was placed in a three-necked flask, where the amount of polytetrahydrofuran diol was 0.5 times that of the liquid crystal unit polyol. About 10 mL of N,N-dimethylformamide (DMF) was added, stirred and dissolved at 100° C. and vacuum dried for 2 h. The temperature was then lowered to 70° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in all polyols and AOH was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants. The mixture was kept at 70° C. for 2 h. 1.5 g of AOH previously dissolved in about 15 mL of DMF was then added, and the temperature was raised to 90° C. The reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70° C. for 48 h. The sample was heat treated at 170°C and 11 MPa for 10 min using a flat vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0104] Comparative Example 1 (Compared with Example 4, the AOH in step (2) was changed to AKL)
[0105] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0106] (2) 9 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. Hexamethylene diisocyanate was added in a nitrogen atmosphere, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AKL was 1.2, and dibutyltin dilaurate accounting for 0.5 wt% of the total reactants was added. The reaction was maintained at 70 ° C for 2 h. 1 g of AKL previously dissolved in about 15 mL of DMF was added, and the temperature was raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0107] Comparative Example 2 (without lignin)
[0108] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the RM82 concentration 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to allow Michael addition reaction to occur, thereby obtaining a crude product of hydroxyl-terminated RM82 liquid crystal unit. Column chromatography was performed using an ethyl acetate / petroleum ether = 5:1 system for gradient elution. When the thin layer chromatography showed an Rf value of 0.2-0.3, the purified liquid crystal polyol product was obtained.
[0109] (2) Take 10g of liquid crystal unit polyol in a three-necked flask, add about 10mL N,N-dimethylformamide (DMF), stir and dissolve at 100℃ and vacuum dry for 2h, cool to 70℃, add hexamethylene diisocyanate in a nitrogen atmosphere, where the molar ratio of -NCO of hexamethylene diisocyanate to hydroxyl group in liquid crystal polyol is 1.2, and dibutyltin dilaurate accounting for 0.5wt% of the total reactants, and keep the temperature at 70℃ for 2h. Then add about 15mL DMF and raise the temperature to 90℃ and continue the reaction for 6h. After the reaction is completed, pour out the product, evaporate the solvent at room temperature for 48h, and then vacuum dry at 70℃ for 48h. Use a flat plate vulcanizer to heat the sample at 170℃ and 11MPa for 10min to obtain a liquid crystal-polyurethane elastomer.
[0110] Comparative Example 3 (Compared with Example 4, polyol, lignin and isocyanate were mixed and reacted in one step)
[0111] (1) 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82) and 3-mercapto-1-propanol (at a molar ratio of 1:2.5) were placed in a two-necked flask, and dichloromethane was added to make the concentration of RM82 0.2 mol / L. Finally, 2 equivalents (based on 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene) of the catalyst triethylamine were added. The nitrogen in the flask was replaced three times, and the mixture was stirred at 25°C for 24 hours to cause Michael addition reaction to obtain a crude product of RM82 liquid crystal unit terminated with hydroxyl group. Column chromatography was performed using ethyl acetate / petroleum ether = 5:1 system for gradient elution. Thin layer chromatography showed that the product R f When the value is 0.2-0.3, the purified liquid crystal polyol product can be obtained.
[0112] (2) 9 g of liquid crystal unit polyol was placed in a three-necked flask, and about 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was stirred and dissolved at 100 ° C and vacuum dried for 2 h. The temperature was then lowered to 70 ° C. 1 g of AOH, which had been previously dissolved in about 15 mL of DMF, was added. Hexamethylene diisocyanate, wherein the molar ratio of -NCO of hexamethylene diisocyanate to the total hydroxyl groups in the liquid crystal polyol and AOH was 1.2, and dibutyltin dilaurate, which accounted for 0.5 wt% of the total reactants, was added in a nitrogen atmosphere. The reaction was maintained at 70 ° C for 2 h. The temperature was then raised to 90 ° C and the reaction was continued for 6 h. After the reaction was completed, the product was poured out, the solvent was evaporated at room temperature for 48 h, and then vacuum dried at 70 ° C for 48 h. The sample was heat-treated at 170 ° C and 11 MPa for 10 min using a flat plate vulcanizer to obtain a lignin-based liquid crystal-polyurethane elastomer.
[0113] The lignin-based liquid crystal-polyurethane elastomer materials of the examples and comparative examples were made into dumbbell-shaped specimens that comply with the GB / T528-2009 standard, and mechanical properties such as tensile strength and elongation at break were tested using an MTS universal testing machine.
[0114] Table 2. Mechanical properties of lignin-based liquid crystal-polyurethane elastomers
[0115]
[0116] Table 2 is the tensile test results of the lignin-based liquid crystal-polyurethane elastomer obtained by the embodiments and comparative examples. As can be seen from Table 2, with the lifting of the lignin dosage (Examples 1-6), the tensile strength of the prepared elastomer samples first increases and then decreases, with the maximum tensile strength reaching 39.11MPa. This is because lignin, while replacing the polyol chain extension, plays the dual role of chemical crosslinking and physical filler. When the lignin dosage is moderate, the lignin in the system has good compatibility with the liquid crystal polymer matrix, so that the material has better tensile strength. When the lignin dosage is further improved, part of the lignin, due to the limited reaction activity and the larger three-dimensional steric hindrance, can be distributed between the polymer segments in the form of filler. It is difficult to produce stress concentration with segment migration during the material stretching process, which is manifested as the lifting of the material modulus and the decline of elongation at break and tensile strength.
[0117] Changing the isocyanate index (Examples 4 and 7-9) increases the interaction between lignin and the liquid crystal polymer backbone, the crosslink density, and the Young's modulus. However, when the R value is too high, the molecular weight of the liquid crystal backbone decreases during the prepolymerization phase, resulting in a shorter crosslinked network within the material. This is detrimental to segment migration during the material's stretching process.
[0118] The introduction of long-chain polyether polyols (Examples 10-11) significantly increased the length of the polymer network's soft segments and overall molecular chain flexibility. The longer chain migration period during stretching resulted in greater energy dissipation, thus improving toughness. However, this also resulted in looser lignin crosslinks, resulting in a decrease in tensile strength. The optimal sample after the introduction of long-chain polyether polyols achieved an elastic recovery rate of 90.1%.
[0119] Comparative Example 1 presents a sample containing industrial alkali lignin. Due to the large molecular weight and wide distribution of alkali lignin (AKL), while it exhibits high reactivity in the early stages of the reaction, the lack of exposed hydroxyl functional groups and excessive steric hindrance make it more likely to interfere with the segment migration ability of the polymer backbone as a chemical crosslinking point. Consequently, the resulting elastomer's mechanical properties are generally inferior to those of the elastomer sample using AOH as a crosslinking agent. Comparative Example 2 presents a liquid crystal polyurethane elastomer without lignin. While the material can be cured into a film, due to the low degree of crosslinking, the segments rely solely on hydrogen bonds and van der Waals forces for skeletal support. These weak bonds are destroyed in the early stages of stretching, resulting in the poorest mechanical properties. Comparative Example 3 presents a sample prepared by one-step polymerization of a liquid crystal polyol, isocyanate, and lignin according to the formulation of Example 4. Compared to the sample prepolymerized and then crosslinked, the material exhibits significantly lower tensile strength and elongation at break. This is because the one-step process reduces the molecular weight of the liquid crystal backbone and increases molecular chain defects. At the same time, the sample prepared in steps in Example 4 can form a more ordered microphase partition, and the uniform cross-linking points and microphase separation structure can improve the mechanical properties of the material.
[0120] In this invention, lignin is covalently linked to the liquid crystal backbone via urethane bonds. Dynamic properties at high temperatures allow for dissociation and reconfiguration. This temperature-stimulated crosslinking reconfiguration is then exploited to program the LCE-PU. The programmed sample exhibited a reversible deformation of 13% under a pre-stress of 0.6 MPa, demonstrating the bidirectional shape memory properties of a liquid crystal elastomer.
[0121] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.
Claims
1. A method for preparing a lignin-based liquid crystal elastomer, characterized in that: The following steps are involved: (1) reacting a liquid crystal unit with a hydroxy mercaptan in the presence of a base catalyst to prepare a hydroxyl-terminated liquid crystal polyol; (2) reacting polyol and isocyanate in the presence of a catalyst to synthesize a liquid crystal-polyurethane prepolymer, then adding lignin to continue the reaction, and drying and hot-pressing the resulting product to obtain a lignin-based liquid crystal elastomer; The polyol is a hydroxyl-terminated liquid crystal polyol, or a mixture of a hydroxyl-terminated liquid crystal polyol and a long-chain polyol; The lignin in step (2) is a specific molecular weight lignin, the weight average molecular weight of which is between 700 and 2000, and the molecular weight distribution index is ≤2.
4.
2. The method for preparing a lignin-based liquid crystal elastomer according to claim 1, characterized in that: The molar ratio of -NCO of the isocyanate to the total hydroxyl groups in the polyol and lignin in step (2) is 1:1 to 1.6:1; and / or, the mass ratio of the lignin to the polyol is 2.5:97.5 to 20:80; And / or, the molar ratio of the long-chain polyol to the hydroxyl-terminated liquid crystal polyol is 0 to 0.5:
1.
3. The method for preparing a lignin-based liquid crystal elastomer according to claim 1 or 2, characterized in that: The liquid crystal cell of step (1) comprises at least one of 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene, 2-methyl-1,4-phenylenebis(4-((11-(acryloyloxy)undecyl)oxy)benzoate), and 1,4-bis-[4-(3-acryloyloxypropoxy)benzoyloxy]-2-methylbenzene; And / or, the hydroxy mercaptan in step (1) includes at least one of 2-mercaptoethanol, 3-mercapto-1-propanol, 5-mercapto-1-pentanol and 6-mercapto-1-hexanol; And / or, the molar ratio of the liquid crystal unit to the hydroxythiol in step (1) is 1:(1.5-3.5).
4. The method for preparing a lignin-based liquid crystal elastomer according to claim 1 or 2, characterized in that: The reaction temperature in step (1) is 0-40° C. and the reaction time is 10-24 hours; and / or, the catalyst in step (1) comprises at least one of triethylamine, di-n-propylamine, triethanolamine, 1,8-diazabicyclo[5.4.0]undec-7-ene and triethylenediamine; And / or, the amount of the catalyst used in step (1) is 1 to 2 equivalents of the liquid crystal unit.
5. The method for preparing a lignin-based liquid crystal elastomer according to claim 1, characterized in that: The long-chain polyol in step (2) comprises at least one of polytetrahydrofuran diol, polycaprolactone diol and polycarbonate diol; and / or, the molecular weight of the long-chain polyol in step (2) is 1000 to 2000; And / or, the isocyanate in step (2) comprises at least one of pentamethylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate and hexamethylene diisocyanate trimer; And / or, the catalyst in step (2) includes a conventional tin catalyst, further including at least one of dibutyltin dilaurate, dibutyltin oxide, didodecylsulfide dibutyltin, stannous octoate and monobutyltin oxide; the amount of the catalyst used accounts for 0.3 to 0.8% of the total mass of the raw materials.
6. The method for preparing a lignin-based liquid crystal elastomer according to claim 1, characterized in that: The temperature of synthesizing the liquid crystal polyurethane prepolymer in step (2) is 60-80° C. and the time is 2-3 hours; And / or, the temperature for continuing the reaction of adding lignin in step (2) is 60-90° C. and the time is 4-7 hours; And / or, the drying in step (2) refers to drying in air first and then drying by heating, wherein the air drying temperature is 10-40°C and the time is 48-72 hours; the heating drying temperature is 55-75°C and the time is 24-48 hours; And / or, the temperature of the hot pressing molding in step (2) is 130-180° C., the pressure is 10-12 MPa, and the time is 15-20 min.
7. The method for preparing a lignin-based liquid crystal elastomer according to claim 1, characterized in that: The reaction medium in step (1) is an organic solvent, which includes at least one of ethyl acetate, dichloromethane, acetone, methanol, tetrahydrofuran and acetonitrile; and / or, the concentration of the liquid crystal unit in the organic solvent is 0.1 to 0.3 mol / L; And / or, the synthesis of the liquid crystal polyurethane prepolymer in step (2) and the addition of lignin to continue the reaction are both carried out under an inert gas atmosphere, wherein the inert gas comprises at least one of nitrogen, argon and helium; And / or, the specific molecular weight lignin in step (2) is obtained by the following method: fully dissolving industrial lignin in an organic solvent, filtering and separating the filtrate, removing the organic solvent from the filtrate, and drying to obtain the specific molecular weight lignin; The temperature of the solvent is 20 to 100° C., and the time is 1 to 10 hours; The concentration of the industrial lignin and the organic solvent after mixing is 100 to 1000 g / L; The industrial lignin includes at least one of enzymatic lignin extracted from ethanol production by fermentation of wood fiber, alkali lignin as a byproduct of alkaline pulping, and organic solvent lignin extracted from wood fiber; The organic solvent comprises at least one of tetrahydrofuran, acetone, butanone, methanol, isopropanol, ethyl acetate, ethanol, ether and hexane, or a mixture of at least one of these solvents and water; And / or, the medium of the reaction in step (2) is a polar organic solvent, and the organic solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide; And / or, the total concentration of the polyol and lignin in the organic solvent in step (3) is 0.1 to 0.4 g / mL.
8. The method for preparing a lignin-based liquid crystal elastomer according to claim 1, characterized in that: The following steps are involved: (1) industrial lignin is mixed with an organic solvent, stirred at 20-100°C for 1-10 hours, filtered and separated, the filtrate is collected and the solvent is removed, and dried to obtain a specific molecular weight lignin; (2) dissolving the liquid crystal unit and the hydroxythiol in an organic solvent, stirring and mixing at 0-40° C., adding a base catalyst, stirring and reacting for 10-24 hours, and purifying the obtained product to obtain a hydroxyl-terminated liquid crystal polyol; (3) Dehydrating the liquid crystal polyol at 90-120° C., then cooling to 60-80° C., adding an organic solvent, a long-chain polyol, a catalyst, and an isocyanate to synthesize a liquid crystal-polyurethane prepolymer, and then adding lignin of a specific molecular weight to the liquid crystal-polyurethane prepolymer, stirring and reacting for 4-7 hours, and curing the resulting product at 10-40° C. for 48-72 hours, and hot pressing at 130-180° C. to obtain a lignin-based liquid crystal elastomer.
9. A lignin-based liquid crystal elastomer obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the lignin-based liquid crystal elastomer according to claim 9.
Citation Information
Patent Citations
Liquid crystal elastomer composition and preparation method thereof
CN118879072A
Near-infrared light response liquid crystal elastomer crosslinked by double dynamic bonds and preparation method of near-infrared light response liquid crystal elastomer
CN119081117A
High-yield preparation method for high-purity low-molecular-weight lignin
CN105198939A
Method for extracting low-molecular-weight lignin from biomass
CN108299517A
Method for extracting low-molecular-weight lignin from walnut shells through graded sedimentation of alkaline tetrahydrofurfuryl alcohol
CN113527710A
Cited By
Molecular chain entangled thermoplastic polyurethane liquid crystal elastomer as well as preparation method and application thereof
CN120718231A
Thermoplastic polyurethane liquid crystal elastomer with molecular chain entanglement and preparation method and application thereof
CN120718231B